2021
DOI: 10.1177/08862605211050103
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Rape Victimization and Perpetration Among National Samples of College Students Across 30 years

Abstract: Research Questions: Rape prevention practice and policy have roots in data from 1985. This study uses 2015 national data to project recent prevalence, assesses whether rates now differ from those of 30 years ago, and disaggregates 2015 prevalence into rape of alcohol incapacitated victims, rapes combining both alcohol and physical tactics, and violent rape. Methods: Cross-sectional analyses were conducted comparing two national samples. The first was collected in 1984-85 (Koss, Gidycz, & Wisniewski, 1987);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Research consistently documents that approximately 50% of sexual assaults involve alcohol consumption by the victim, perpetrator, or both (Abbey et al, 2014). Moreover, these rates have increased over time, in part due to perpetrator exploitation of victims who are incapacitated (i.e., unable to provide consent) due to alcohol consumption (Koss et al, 2022). A U.S. national sample of college women reported that most alcohol-/drug-facilitated rapes (72%) involved alcohol only, 21% of alcohol-/drug-facilitated rapes involved alcohol and drugs, and 7% of alcohol-/drug-facilitated rapes involved drugs only (McCauley et al, 2009).…”
Section: Alcohol-involved Rapementioning
confidence: 99%
“…Research consistently documents that approximately 50% of sexual assaults involve alcohol consumption by the victim, perpetrator, or both (Abbey et al, 2014). Moreover, these rates have increased over time, in part due to perpetrator exploitation of victims who are incapacitated (i.e., unable to provide consent) due to alcohol consumption (Koss et al, 2022). A U.S. national sample of college women reported that most alcohol-/drug-facilitated rapes (72%) involved alcohol only, 21% of alcohol-/drug-facilitated rapes involved alcohol and drugs, and 7% of alcohol-/drug-facilitated rapes involved drugs only (McCauley et al, 2009).…”
Section: Alcohol-involved Rapementioning
confidence: 99%
“…Male-initiated sexually aggressive behavior (SAB) toward women is a serious public-health problem on college campuses across the United States (Koss et al, 2022). Approximately 25% of college women report being sexually assaulted by a man during college (Cantor et al, 2019).…”
Section: Normative Misperception Of Sex- and Alcohol-related Attitude...mentioning
confidence: 99%
“…First, perceived peer approval of and engagement in contact SAB predicts contact SAB (Jacques-Tiura et al, 2015; Swartout, 2013; Thompson et al, 2015). Alcohol consumption is also linked to contact SAB, with 50%–75% of contact SAB episodes occurring when the victim, perpetrator, or both have consumed alcohol (Abbey et al, 2014; Koss et al, 2022). However, many SAB proximal predictor variables traditionally have not incorporated the presence of alcohol.…”
Section: Normative Misperception Of Sex- and Alcohol-related Attitude...mentioning
confidence: 99%
“…Sexual aggression, defined as any attempted or completed sexual activity against a person's will, is a prevalent problem among college students (Koss et al, 2022;Krahé 2021), with a wide range of potential physical, mental, and behavioral problems (Dworkin et al, 2017(Dworkin et al, , 2022Ullman & Najdowski, 2011), and a higher vulnerability to revictimization (Anderson et al, 2020;Cusack et al, 2021). Prevention approaches to reduce the rates of sexual aggression perpetration and victimization were mostly developed in the United States and were tailored to the context of campus universities.…”
Section: Introductionmentioning
confidence: 99%